Structural biology and bioinformatics in drug design: opportunities and challenges for target identification and lead discovery - Blundell, Tom L; Sibanda, Bancinyane L; Montalvão, Rinaldo Wander; Brewerton, Suzanne; Chelliah, Vijayalakshmi; Worth, Catherine L; Harmer, Nicholas J; Davies, Owen; Burke, David (Philosophical transactions of the Royal Society of London. Series B. Biological sciences, 2006)
Impressive progress in genome sequencing, protein expression and high-throughput crystallography and NMR has radically transformed the opportunities to use protein three-dimensional structures to accelerate drug discovery, but the quantity and complexity of the data have ensured a central place for informatics. Structural biology and bioinformatics have assisted in lead optimization and target identification where they have well established roles; they can now contribute to lead discovery, exploiting high-throughput methods of structure determination that provide powerful approaches to screening of fragment binding.